PENGARUH CURRENT RATIO, DEBT RATIO, TOTAL ASETS TURNOVER, RETURN ON ASSETS, RETURN ON EQUITY, CURRENT LIABILITY TO TOTAL LIABILITY, DAN FIXED ASSET TO TOTAL ASSETS TERHADAP KESEHATAN PERUSAHAAN MANUFAKTUR DI INDONESIA (STUDI PADA PERUSAHAAN MANUFAKT - Sekti, Binastya Anggara (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
The background of this research is many manufacturing companies in Indonesia that went bankrupt due to the multi-dimensional crisis since 2008, and to show than financial statement analysis can predict the financial health of the company to help provide an overview of financial strength in order to perform the appropriate actions and avoid bankruptcy. The objective of this research is to predict level of healthy of financial ability the manufacturing company is in bankruptcy categorized or not. The design of this research applies on many manufacturing company which listed on the Indonesian Stock Exchange which have been listed from 2009 to 2013. Data analysis applied measuring method on purposive sampling or sampling by taking the number of objects in accordance with the intended purpose. Data processing used logistic regression method. The result of research indicated that Current Ratio, Debt Ratio, Total Asset Turnover Ratio and Fix Asset to Total Asset ratio, cannot predict the occurrence of financial healthy in the manufacturing companies listed on the Indonesia Stock Exchange. While the Return on Assets, Return on Equity and Current Liability to Total Liability Ratio can predict the occurrence of bankruptcy probability in the manufacturing companies listed on the Indonesian Stock Exchange.Â Kata Kunci Rasio keuangan, laporan keuangan, kesehatan perusahaan, regresi logistik.